2021
DOI: 10.5802/alco.165
|View full text |Cite
|
Sign up to set email alerts
|

Maximally nonassociative quasigroups via quadratic orthomorphisms

Abstract: We show that, with finitely many exceptions, there exists a maximally nonassociative quasigroup of order n whenever n is not of the form n = 2p 1 or n = 2p 1 p 2 for primes p 1 , p 2 with p 1 p 2 < 2p 1 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…We also found that there are 7q232+O(q32) $7{q}^{2}\unicode{x02215}32+O({q}^{3\unicode{x02215}2})$ quadratic N2 ${N}_{2}$ Latin squares of order q $q$. Drápal and Wanless [12] showed that the quadratic Latin squares MJX-tex-caligraphicscriptL[a,b] ${\rm{ {\mathcal L} }}[a,b]$ and MJX-tex-caligraphicscriptL[c,d] ${\rm{ {\mathcal L} }}[c,d]$ of order q $q$ are isomorphic if and only if {c,d}={θ(a),θ(b)} $\{c,d\}=\{\theta (a),\theta (b)\}$ for an automorphism θ $\theta $ of Fq ${{\mathbb{F}}}_{q}$. It follows that the number of isomorphism classes of N2 ${N}_{2}$ quadratic Latin squares of order q $q$ is at least normalΘ(q2log(q)) ${\rm{\Theta }}({q}^{2}\unicode{x02215}\mathrm{log}(q))$.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We also found that there are 7q232+O(q32) $7{q}^{2}\unicode{x02215}32+O({q}^{3\unicode{x02215}2})$ quadratic N2 ${N}_{2}$ Latin squares of order q $q$. Drápal and Wanless [12] showed that the quadratic Latin squares MJX-tex-caligraphicscriptL[a,b] ${\rm{ {\mathcal L} }}[a,b]$ and MJX-tex-caligraphicscriptL[c,d] ${\rm{ {\mathcal L} }}[c,d]$ of order q $q$ are isomorphic if and only if {c,d}={θ(a),θ(b)} $\{c,d\}=\{\theta (a),\theta (b)\}$ for an automorphism θ $\theta $ of Fq ${{\mathbb{F}}}_{q}$. It follows that the number of isomorphism classes of N2 ${N}_{2}$ quadratic Latin squares of order q $q$ is at least normalΘ(q2log(q)) ${\rm{\Theta }}({q}^{2}\unicode{x02215}\mathrm{log}(q))$.…”
Section: Discussionmentioning
confidence: 81%
“…The condition {ab,(a1)(b1)}Rq $\{ab,(a-1)(b-1)\}\subseteq {{\rm{ {\mathcal R} }}}_{q}$ ensures that MJX-tex-caligraphicscriptL[a,b] ${\rm{ {\mathcal L} }}[a,b]$ is a Latin square [16]. Quadratic Latin squares have previously been used to construct perfect 1‐factorisations [1, 17, 38], mutually orthogonal Latin squares [15, 16], atomic Latin squares [38], Falconer varieties [1] and maximally nonassociative quasigroups [10, 11]. Quadratic Latin squares are the main focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) b = a/(2a − 1) and (q, a) ∈ {(13, 2), (13,9), (17,5), (17,8), (37,11), (37,27), (41, 23), (41, 26)}.…”
Section: N 2 Quadratic Latin Squaresmentioning
confidence: 99%
“…Such squares are called quadratic Latin squares. Quadratic Latin squares have previously been used to construct perfect 1-factorisations [34,15,1], mutually orthogonal Latin squares [14,13], atomic Latin squares [34], Falconer varieties [1], and maximally non-associative quasigroups [9,10]. Quadratic Latin squares are the main focus of this paper.…”
Section: Introductionmentioning
confidence: 99%